Tents pitched on the edge of Middle Lake, White Pass Trail, British Columbia. - Curtis, Asahel, 1874-1941 (1898)
"This camp, 8 miles beyond the summit, was in the first timber on the Yukon side. Swept by fierce storms of the Coast Range, it was the most desolate camp on the Skagway [White Pass] Trail." Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number